Timing Evidence for Symbolic Phonological Representations and Phonology-Extrinsic Timing in Speech Production - Turk, Alice; Shattuck-Hufnagel, Stefanie (Frontiers in Psychology, 2020)
The goals of this paper are (1) to discuss the key features of existing articulatory models of speech production that govern their approaches to timing, along with advantages and disadvantages of each, and (2) to evaluate these features in terms of several pieces of evidence from both the speech and nonspeech motor control literature. This evidence includes greater timing precision at movement endpoints compared to other parts of movements, suggesting the separate control of the timing of movement endpoints compared to other parts of movement. This endpoint timing precision challenges models in which all parts of a movement trajectory are controlled by the same equation of motion, but supports models in which (a) abstract, symbolic phonological representations map onto spatial and temporal characteristics of the part(s) of movement most closely related to the goal of producing a planned set of acoustic cues to signal the phonological contrast (often the endpoint), (b) movements are coordinated primarily based on the goal-related part of movement, and (c) speakers give priority to the accurate implementation of the part(s) of movement most closely related to the phonological goals. In addition, this paper presents three types of evidence for phonology-extrinsic timing, suggesting that surface duration requirements are represented during speech production. Phonology-extrinsic timing is also supported by greater timing variability for repetitions of longer intervals, assumed to be due to noise in a general-purpose (and phonology-extrinsic) timekeeping process. The evidence appears to be incompatible with models that have a unified Phonology/Phonetics Component, that do not represent the surface timing of phonetic events, and do not represent, specify and track timing by general-purpose timekeeping mechanisms. Taken together, this evidence supports an alternative approach to modeling speech production that is based on symbolic phonological representations and general-purpose, phonology-extrinsic, timekeeping mechanisms, rather than on spatio-temporal phonological representations and phonology-specific timing mechanisms. Thus, the evidence suggests that models in that alternative framework should be developed, so they can be tested with the same rigor as have models based on spatio-temporal phonological representations with phonology-intrinsic timing.